Synthesis and Characterization of Surfactant for Retarding Acid–Rock Reaction Rate in Acid Fracturing - Yan, Fuli; Shi, Yongmin; Tian, Yu (Frontiers in Chemistry, 2021)
Acid fracturing is an effective method to develop ultra-low permeability reservoirs. However, the fast reaction rate reduces the effect of the acid fracturing and increases the near-well collapse risk. Therefore, it is necessary to retard the acid-rock reaction rate. In this work, we synthesized an acid-resistant Gemini-zwitterionic viscoelastic surfactant (named VES-c), which has good performances such as temperature resistance, salt resistance, and shear resistance. Besides, low concentration of VES-c increases the viscosity of the acid solution. The CO2 drainage method was used to measure the reaction rate between the dibasic acid and dolomite/broken core. We find that the dibasic acid containing 0.3% VES-c retards the dolomite reaction rate of 3.22 times compared with only dibasic acid. Furthermore, the dibasic acid containing 0.3% VES-c exhibits uniform distribution and is not easy to adhere to the solid surface. The VES-c also is favorable to reduce the formation of amorphous calcium carbonate. Retarding the rate of acid-rock reaction and enhancing the acidification are mainly attributed to VES-c’s viscosity-increasing, salt-tolerance, and anti-adsorption. Hopefully, this kind of surfactant retarding reaction rate is applied to other acid-rock reactions.